KELAYAKAN POSTER MATERI KEANEKARAGAMAN HAYATI DARI BUAH BERANTE’, LAMPAHUNG DAN PANSI’ - Sianus, Evo; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of poster media from the results of morphology, nutrient content and fruit fiber of Berante (Sumbaviopsis albicans (Blume) JJSm.), Lampahung (Baccaurea racemosa Muell. Arg) and Pansi '(Xanthophyllum flavescens Roxb.) in the Tembawang forest Bagak, Sahan Village, Bengkayang District on biodiversity material for class X high school. The research was descriptive using purposive sampling technique with two stages, namely instrument validation and media validation. The poster media was validated by five validators with 12 criteria and was calculated using the Analysis of Content Validity Ratio (CVR) and Lawshe Content Validity Index (CVI). The poster media was validated by 5 validators, namely two lecturers of the Biology Education Study Program FKIP Untan and two biology teachers in class X SMA Bengkayang District and one biology teacher in class X in Pontianak. Instrument validation results showed a validation sheet was used and corrected while the results of poster media validation obtained CVR and CVI values of 0.99 which corresponded to the minimum Lawshe value for five validators, so the posters was declared valid and feasible to be used as learning media on biodiversity material in class X high school.Keywords : Posters, Biodiversity, Berante ', Lampahung, Pansi'